Quality of Life in Vestibular Schwannoma Patients Managed by Surgical or Conservative Approaches. Issue 7 (August 2015) - Jufas, Nicholas; Flanagan, Sean; Biggs, Nigel; Chang, Phillip; Fagan, Paul
<x xml:space="preserve">Abstract</x> Objective The aim of our study was to assess quality of life (QOL) among patients who underwent microsurgical excision of vestibular schwannoma (VS) compared with those managed conservatively. Study Design Retrospective study. Setting Tertiary care center. Patients There was a total sample population of 376 patients diagnosed with a unilateral VS. Intervention A total of 223 patients with unilateral VS returned the mailed questionnaires. These were then divided into two groups—78 that had undergone microsurgical excision and 145 that were managed conservatively. Subgroups within these primary groups were created for analysis. Main Outcome Measure The primary outcome measure was the Medical Outcomes Study 36 Items Short Form (SF-36). The Dizziness Handicap Inventory test, Hearing Handicap Inventory test, and Tinnitus Handicap Inventory were also used. Results The surgically managed group had a worse QOL when compared with the conservatively managed group using SF-36, significantly so in the domains of physical role limitation and social functioning. Trends were seen toward a better QOL in some domains in the subgroups of male patients and patients younger than 65 years. Worse QOL scores in the Tinnitus Handicap Inventory were seen in the subgroups with larger tumor size. Finally, on correlation analysis between all handicap inventories and SF-36, handicap due to disequilibrium had the strongest correlation with worsening of QOL. In SF-36, the vitality domain showed the greatest correlation with otologic handicap overall, whereas the role emotional domain showed the least. Conclusion This study found that worse QOL scores for surgically managed versus conservatively managed VS patients are most significant in the areas of physical role limitation and social functioning. In some areas, patients who are male and younger report better QOL. Handicap due to disequilibrium seems to have the greatest negative impact on QOL. These factors should be considered when counseling patients regarding approach to VS, in the context of an experienced management program.